2008
DOI: 10.1016/j.jacc.2008.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Different Gadolinium Enhancement Patterns in Patients After Heart Transplantation

Abstract: CE-MRI allows identification of silent MI in apparently event-free HTX patients and is able to disclose myocardial fibrosis already in patients with absent or mild angiographic TCAD. CE-MRI might be helpful to establish an earlier TCAD diagnosis and to intensify medical treatment. Future studies are necessary to test prognostic implications associated with CE-MRI patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 26 publications
2
35
2
Order By: Relevance
“…We found a high prevalence of myocardial scar in heart transplantation patients, confirming what has been described previously in other heart transplant populations (7,13,22). Very little is known about the development or progression of myocardial scar in HTRs.…”
Section: Discussionsupporting
confidence: 90%
“…We found a high prevalence of myocardial scar in heart transplantation patients, confirming what has been described previously in other heart transplant populations (7,13,22). Very little is known about the development or progression of myocardial scar in HTRs.…”
Section: Discussionsupporting
confidence: 90%
“…35 More recent data, using the robust clinical tool of myocardial LGE, showed that 84% of patients with severe CAV on angiography had typical infarct-pattern subendocardial LGE with a distribution consistent with the pattern of CAV on angiography. 36 Despite these encouraging results, there remains a paucity of data on MRI in this setting, and no firm recommendations can be made without further comprehensive prospective trials. 26 For coronary LGE, as with any new technique, there will be a learning curve for acquisition, analysis, and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the cutoff value of <1.3 used for the detection of patients with poor outcomes is close to 1.4, which was selected as cutoff value for CAV detection (8). Different patterns of both infarct-related and infarct-atypical LGE on the other hand, were previously demonstrated in HT recipients and were shown to be associated with the degree of CAV (11). In our study, LGE was observed in 33 (31%) patients and a trend was noted for cardiac events in the presence of either typical or atypical LGE patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Late gadolinium enhancement (LGE) images were scored visually using a 17-segment model. Hereby, both ischemic (infarctrelated) and atypical noninfarct-related patterns of LGE were analyzed (11).…”
Section: Cmr Examinationmentioning
confidence: 99%